T6SS4 is heterogeneously expressed in Yersinia pseudotuberculosis and is a target for transcriptional and post-transcriptional regulation - Kerwien, Anna; Körner, Britta; Meyer, Ines; Teschke, Yannick; Köster, Cassandra Sophie; Salto, Ileana Paula; Dersch, Petra; Herbrüggen, Anne-Sophie (PLOS Pathogens, 2025)
The type VI secretion system (T6SS) is a complex secretion system encoded by many Gram-negative bacteria to translocate effector proteins directly into target cells. Due to its high complexity and energy-intensive firing process, regulation of the T6SS is tightly controlled in many organisms. Y. pseudotuberculosis encodes four complete T6SS clusters but lacks genes implicated in T6SS gene regulation in other microorganisms, indicating a distinct control mechanism. Here, we could show that the T6SS4 of Y. pseudotuberculosis is heterogeneously expressed within a population, which is determined by the transcriptional T6SS4 activator RovC. Moreover, the T6SS4 and RovC are embedded in a complex and global regulatory network, including the global post-transcriptional regulator CsrA, the Yersinia modulator A (YmoA), the global protease Lon, and RNases (PNP and RNase III). Post-transcriptional processing of the T6SS4 polycistron and different transcript stability within the operon also achieve a higher regulatory complexity. In summary, our work provides new insights into the sophisticated and complex regulatory network of the T6SS4 of Y. pseudotuberculosis, which clearly differs from regulation in other organisms.